Monosodium urate monohydrate crystals inhibit osteoblast viability and function: implications for development of bone erosion in gout. Issue 9 (27th May 2011) - Chhana, Ashika; Callon, Karen E; Pool, Bregina; Naot, Dorit; Watson, Maureen; Gamble, Greg D; McQueen, Fiona M; Cornish, Jillian; Dalbeth, Nicola
Abstract : Background: Bone erosion is a common manifestation of chronic tophaceous gout. Objectives: To investigate the effects of monosodium urate monohydrate (MSU) crystals on osteoblast viability and function. Methods: The MTT assay and flow cytometry were used to assess osteoblast cell viability in the MC3T3-E1 and ST2 osteoblast-like cell lines, and primary rat and primary human osteoblasts cultured with MSU crystals. Quantitative real-time PCR and von Kossa stained mineralised bone formation assays were used to assess the effects of MSU crystals on osteoblast differentiation using MC3T3-E1 cells. The numbers of osteoblasts and bone lining cells were quantified in bone samples from patients with gout. Results: MSU crystals rapidly reduced viability in all cell types in a dose-dependent manner. The inhibitory effect on cell viability was independent of crystal phagocytosis and was not influenced by differing crystal length or addition of serum. Long-term culture of MC3T3-E1 cells with MSU crystals showed a reduction in mineralisation and decreased mRNA expression of genes related to osteoblast differentiation such as Runx2, Sp7 (osterix), Ibsp (bone sialoprotein), and Bglap (osteocalcin). Fewer osteoblast and lining cells were present on bone directly adjacent to gouty tophus than bone unaffected by tophus in patients with gout. Conclusions: MSU crystals have profound inhibitory effects on osteoblast viability and differentiation. These data suggest that bone erosion in gout occurs at the tophus–bone interface through alteration of physiological bone turnover, with both excessive osteoclast formation, and reduced osteoblast differentiation from mesenchymal stem cells.